Blood-nerve barrier disruption and coagulation system activation induced by mechanical compression injury participate in the peripheral sensitization of trigeminal neuralgia - Zhou, Lu-Xi; Lin, Shao-Wei; Qiu, Rong-Hui; Lin, Ling; Guo, Yue-Feng; Luo, Dao-Shu; Li, Yun-Qing; Wang, Feng (Frontiers in Molecular Neuroscience, 2022)
Microvascular compression in the trigeminal root entry zone (TREZ) is the main cause of primary trigeminal neuralgia (TN). However, the precise mechanism of TN is inconclusive. In this study, we observed that compression injury of rat TREZ successfully induced the TN like behavior, accompanied by destroying the permeability of blood nerve barrier (BNB) and promoting the expression of prothrombin and thrombin inhibitor protease nexin-1 (PN-1). Besides, it was also observed that the expression of paranodal proteins neurofascin-155 (NF155) and neurofascin-125 (NF125) increased, while the nodal gap length of nodes of Ranvier widened and the length of node-depleted zones shortened. Moreover, the expression of protease-activated receptor 1 (PAR1) within TREZ was up-regulated at an early stage of TN, and administration of PAR1 antagonist SCH79797 effectively ameliorated the orofacial mechanical allodynia. These results suggested that compression injury of TREZ increased the permeability of the BNB and induced the disturbance of local coagulation-anticoagulation system, concomitant with the structural changes of nodes of Ranvier, thrombin-PAR1 may play a critical role in modulating the orofacial mechanical hyperalgesia in the TN rat model.